AN ANALYSIS OF GROWTH AND ASSOCIATION BETWEEN LABOUR PRODUCTIVITY AND WAGES IN THE INDIAN LEATHER INDUSTRY (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The leather industry is one of India’s oldest  industrial industries and plays a significant role  in the Indian economy. It employs over 2.5  million people in the country and generates  roughly $ 5 million in annual revenue. Because  of its abundant raw materials, India is one of the  best places in the world to invest in the leather  business. Therefore, it is essential to follow the  development of India’s leather industry. This  article is It was the first attempt to analyze the  growth and composition of the workforce in  the Indian leather industry using the annual  compound interest growth rate. Second, clarify  the relationship between the growth of the  Indian leather industry and employment, wages  and net value added (NVA). Finally, we used  regression analysis to analyze the impact of labor  productivity on wage setting. The individual  NIC codes (151 and 152) were chosen to draw  inferences between these 2 codes to give an  overview of the leather industry.
Keywords: Leather; Labour Productivity; Employment Growth; Regression; Wage